Engineering multifunctional bactericidal nanofibers for abdominal hernia repair - Samson Afewerki (Nature Portfolio, 2021)
Afewerki et al. employ integrated electrospinning, plasma treatment and direct surface modification strategy to engineer multifunctional bactericidal nanofibers for use in hernia repair. In a mouse model, they demonstrate that these nanofibers display good biological performance with low inflammatory response, good biodegradation and optimal collagen and blood vessel formation and tissue growth.